A method for preparing a graphene composite biomass micro-nano cavity heat sink

Through the preparation method of the thermal plate of graphene composite biomass micro -nano -cavity, the existing high heat -conducting materials cannot meet the problem of high heat flow density heat transfer needs of electronic devices, and realize the efficient heat dissipation of lightweight, easy processing and low cost. Effect.

CN114885583BActive Publication Date: 2025-01-21XINGTU (CHANGZHOU) CARBON MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210539382.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-18
Publication Date
2025-01-21
Estimated Expiration
2042-05-18

AI Technical Summary

Technical Problem

Existing high-thermal conductivity materials cannot meet the demand for high heat flow density heat transfer in electronic devices, especially after the popularization of 5G products, the demand for high-end heat dissipation devices in electronic products has increased.

Method used

The graphene composite biomass micro -nanocaic cavity is a thermal plate. The composite biomass micro -nanocaic cavity is used as a variable material diversion channel, and the bronze foil and alloy materials are replaced by graphene heat -guiding film to achieve the heat of carbon -based composite materials to the metal base. Replacement of board.

Benefits of technology

It realizes lightweight, easy processing and low cost, and is suitable for large -scale production of commercial and industrialization, which can meet the cooling demand for high heat flow density of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114885583B_ABST
    Figure CN114885583B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a graphene composite biomass micro-nano cavity heat spreader, comprising: (1) cutting wood into thin slices and soaking them in a dilute ammonia solution, reflux treatment to remove gum and fatty acids in pine wood, and then carbonizing them to obtain a flaky porous biomass carbon material with a straight channel structure; (2) hot melt paraffin microchannel impregnation and encapsulation to prepare a phase change micro-nano cavity; (3) drying graphene oxide slurry into a film, cutting, and graphitizing at 2600-3000°C to obtain a graphene foam film; (4) assembling the micro-nano cavity with a graphene thermal conductive film. The present invention uses a composite biomass micro-nano cavity as a phase change material guide channel of a heat spreader, and uses a graphene thermal conductive film instead of copper foil and alloy materials for packaging, thereby realizing the replacement of a metal-based heat spreader with a carbon-based composite material, and making important breakthroughs in terms of lightweight heat dissipation devices and easy material processing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of heat dissipation of electronic equipment, and in particular to a method for preparing a graphene composite biomass micro-nano cavity heat spreader. Background Art

[0002] With the development of electronic technology, mobile electronic products and high-end electronic products are becoming more and more popular, and the size of electronic products is getting smaller and smaller. The existing high thermal conductivity materials, such as ordinary copper and aluminum profile heat dissipation devices, can no longer meet the needs of high heat flux density heat transfer of electronic devices. In the fields of electronics, communications, aerospace, automated mechanical equipment, etc., especially with the advent of 5G products, mobile electronic products have higher and higher requirements for high-precision ultra-thin heat dissipation devices. When 5G processes high-speed and large-capacity data, mobile phone terminals will generate ultra-high heat, and better thermal conductivity devices are needed to meet the heat transfer needs of high heat flux density. The heat dissipation problem has become one of the core factors restricting the development of high-end electronic devices. Phase change heat conduction is the most efficient heat conduction method today. The heat spreader is a typical product of phase change heat conduction. It is also the best way to solve the current high heat flux density problem of electronic chips. It relies on the latent heat of vaporization during the vaporization and condensation process of liquid to achieve heat transfer. The thermal conductivity of phase change heat transfer elements far exceeds that of traditional heat dissipation devices. Its thermal conductivity is greater than 5000W / m K, which is dozens of times higher than that of traditional heat conduction methods (the thermal conductivity coefficients of air convection and liquid convection are 10-100 and 100-1000W / m K, respectively). It has been widely used in high-end graphics cards, laptops, servers, and smart phones.

[0003] In electronic products, the size of chips and the entire product is getting smaller and smaller. In order to improve the heat dissipation effect, laptops, servers, high-end graphics cards, etc. all use phase change thermal conductive devices. At present, the mainstream thermal conductive components of smartphones are a combination of graphite sheets and copper sheets. For example, Huawei uses alloys with high thermal conductivity. However, with the improvement of chip performance, traditional thermal conductive materials are increasingly difficult to meet performance requirements. Currently, Huawei, Samsung, etc. have taken the lead in using ultra-thin heat pipe thermal conductive technology in their high-end mobile phones and have achieved good results. At present, only a few companies have mastered ultra-thin heat pipes and heat spreaders, such as Qihong, Shuanghong, Chaozhong, Jiance, Taishuo, etc. Generally, small and medium-sized heat dissipation product manufacturers cannot produce ultra-thin heat pipes and ultra-thin heat spreaders.

[0004] With the popularization of 5G products, the performance of device function modules has been improved, the integration has increased, and the power consumption has increased significantly. The demand for high-end heat dissipation devices has remained strong. As the demand for thin, ultra-small, green and environmentally friendly heat dissipation devices has increased significantly, lightweight heat dissipation devices have also been put on the agenda. Once lightweight heat dissipation devices are industrialized, electronic product heat dissipation devices will usher in upgrades and can quickly occupy the market through technical and cost advantages and obtain huge profits. Its prospects are very broad. Summary of the invention

[0005] In view of the above problems, the present invention provides a method for preparing a graphene composite biomass micro-nano cavity heat spreader, using the composite biomass micro-nano cavity as the phase change material guide channel of the heat spreader, and using graphene thermal conductive film instead of copper foil and alloy materials for packaging, thereby realizing the replacement of metal-based heat spreaders with carbon-based composite materials, making important breakthroughs in lightweight heat dissipation devices and easy material processing. The graphene composite biomass micro-nano cavity heat spreader is low in cost and more suitable for large-scale commercial and industrial production.

[0006] The technical solution of the present invention is: a method for preparing a graphene composite biomass micro-nano cavity heat sink, characterized in that:

[0007] (1) Preparation of sheet-like porous biomass carbon materials with straight pore structures

[0008] The wood is cut into thin slices and soaked in a dilute ammonia solution, refluxed at 100-150°C to remove gum and fatty acids in the pine wood, and then carbonized at 800-1200°C to obtain a flaky porous biomass carbon material with a straight pore structure;

[0009] (2) Preparation of phase-change micro-nano cavity sequence sheets by hot-melt wax microchannel impregnation

[0010] The flaky porous biomass carbon material obtained in step (1) is placed in molten paraffin for immersion, and vacuum dried to obtain a phase change micro-nano cavity sequence sheet impregnated and encapsulated with hot melt paraffin microchannels;

[0011] (3) Preparation of graphene thermal conductive film

[0012] The graphene oxide slurry is dried to form a film, cut, and graphitized at 2600-3000°C to obtain a graphene foam film, which is then calendered to obtain a graphene thermal conductive film, which is then die-cut and formed, and the edge bonding position is bonded with a thermal conductive adhesive;

[0013] (4) Graphene thermal conductive film coated micro-nano cavity assembly to prepare heat spreader

[0014] The phase change micro-nano cavity sequence sheet obtained in step (2) and the graphene thermal conductive film obtained in step (3) are placed in a mold, the gaps are filled with liquid paraffin, and vacuum pressed to obtain a graphene composite biomass micro-nano cavity heat spreader.

[0015] The wood material for step (1) is selected from pine, fir, cypress and other coniferous species as raw materials, and the slicing method is flat cutting or ring cutting to obtain wood chips with short-diameter dense array tubes, or vertical cutting to obtain wood chips with long-diameter sparse array tubes.

[0016] The flakes are treated in step (1) by soaking in a 3-10 wt% dilute ammonia solution, refluxing in an oil bath at 100-150° C. for 5-8 hours, washing with water 3-5 times, and removing free water from the wood chips by vacuum freeze drying.

[0017] In step (1), the carbonization temperature of the wood chips is set at 800-1200°C, and the heating rate is preferably 2°C min -1 The cooling rate is preferably 5℃min -1 The heat preservation time at the highest temperature is 3-5h, and the surface shrinkage ratio of the log and the carbonized porous carbon material is 3:1-5:1.

[0018] The paraffin wax in step (2) preferably has a melting point of 47-64°C and a density of about 0.9 g / cm 3 Commercial paraffin wax, the conditions for injecting paraffin wax into the porous biomass carbon material tube are as follows: the paraffin wax is heated to 80-120℃ until it is molten and fully impregnated with the porous biomass carbon material for 3-5h, the ambient temperature is set to 80-100℃, and the vacuum negative pressure is set to 5-15Mpa.

[0019] In the step (2), preferably, 3-5wt% graphene oxide slurry is coated by a doctor blade with a blade spacing of 3-5mm, and dried at 70-90°C to form a film to obtain a graphene oxide film with a thickness of 200-380μm. The graphene oxide film is cut and graphitized at 2600-3000°C under argon protection to obtain a graphene foam film, which is then calendered to obtain a density of 1.8-2.0g / cm 3 Graphene thermal conductive film with a thickness of 40-80μm.

[0020] In the step (4), the graphene thermal conductive film is die-cut according to the size of the nanocavity sequence sheet, and the edge is annularly bonded with a 1-3 mm wide thermal conductive adhesive. The order of placement in the mold is: graphene thermal conductive film paste, phase change micro-nano cavity sequence sheet impregnated and encapsulated with hot-melt paraffin microchannels, and graphene thermal conductive film paste. The vacuum pressure of the vacuum press is set to 5-15 MPa, the vacuuming time is 3-5 minutes, and the mold is pressed together with the adhesive position to seal.

[0021] Preferably, the present invention specifically comprises the following steps:

[0022] (1) Cut pine wood into thin slices and soak them in a dilute ammonia solution with a concentration of 3-10wt%, and reflux them in an oil bath at 100-150°C for 5-8h to remove gum, fatty acids and other substances in the pine wood. After removing the gum, the wood chips are washed 3-5 times, and free water in the wood chips is removed by vacuum freeze drying; the wood chips are placed in a tubular furnace under the protection of high-purity argon gas and subjected to carbonization treatment at a temperature of 800-1200°C, with a heating rate of 2°C min -1 , cooling rate 5℃min -1, the heat preservation time at the highest temperature is 3-5h, and a flaky porous biomass carbon material with a straight pore structure is obtained;

[0023] (2) heating the paraffin wax to 80-120° C. in an oil bath until the paraffin wax is molten, placing the flaky porous biomass carbon material obtained in step (1) in the paraffin wax and immersing for 3-5 hours, placing the paraffin wax and the flaky porous biomass carbon material in a vacuum drying oven, setting the temperature to 80-100° C. and the vacuum degree to 5-15 MPa, and standing in the oven to dry, thereby obtaining a phase change micro-nano cavity sequence sheet impregnated and encapsulated with hot melt paraffin wax micro-channels; the conductivity graphs of the biomass nanocavities obtained under the carbonization treatment at different temperatures in step (1) are shown in FIG. Figure 2 As shown;

[0024] (3) 3-5wt% graphene oxide slurry is coated by a doctor blade with a blade spacing of 3-5mm, and dried at 70-90°C to form a film to obtain a graphene oxide film with a thickness of 200-380μm. The graphene oxide film is cut and graphitized at 2600-3000°C under argon protection to obtain a graphene foam film, which is calendered to obtain a density of 1.8-2.0g / cm 3 A graphene thermal conductive film with a thickness of 40-80 μm is used as a packaging shell; the graphene thermal conductive film is die-cut according to the size of the phase change micro-nano cavity sequence sheet impregnated with hot-melt paraffin microchannels, and the edge bonding position is bonded with thermal conductive glue;

[0025] (4) placing the phase change micro-nano cavity obtained in step (2) and the graphene thermal conductive film obtained in step (3) into a mold, filling the gap with liquid paraffin, and performing vacuum pressing treatment at 25° C. for 10-30 min using a vacuum press to obtain a graphene composite biomass micro-nano cavity heat spreader.

[0026] The working principle of the graphene composite biomass micro-nano cavity heat sink of the present invention is as follows: Figure 5 (Vertical cut biomass micro-nano cavity heat sink), Figure 6 (Cross-section of biomass micro-nano cavity heat sink) as shown.

[0027] The technical effects of the present invention are:

[0028] 1. A heat spreader is prepared using paraffin as a phase change material, a biomass carbon material nano-bin as a phase change material guide tube, and a graphene thermal conductive film as the carbon base of the packaging shell. The prepared heat spreader is green and environmentally friendly, lightweight, and easy to process, and is suitable for large-scale commercial and industrial production.

[0029] 2. The graphene composite heat spreader prepared by the present invention can realize customized and controllable thickness of the heat spreader through adjusting the size of the micro-nano cavity sequence sheet and the graphene thermal conductive film. The paraffin phase change micro-nano cavity combined with the excellent in-plane thermal conductivity of the graphene thermal conductive film can meet the large-flux heat dissipation requirements of power devices in electronic equipment. The new graphene composite heat spreader is a technological innovation and product replacement for the current mainstream copper heat pipes, heat spreaders and other heat dissipation component products. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a real picture of the surface of the pine wood chip after carbonization;

[0031] Figure 2 is the conductivity graph of biomass nanocavity treated with different heat levels;

[0032] Figure 3 This is a physical picture of graphene thermal conductive film;

[0033] Figure 4 This is a cross-sectional SEM image of the graphene thermal conductive film;

[0034] Figure 5 This is the working principle diagram of the graphene composite vertically cut biomass micro-nano cavity heat sink;

[0035] Figure 6 This is the working principle diagram of the graphene composite cross-section biomass micro-nano cavity heat sink;

[0036] Figure 7 Thermal drop curve of graphene composite biomass micro-nano cavity vapor chamber test;

[0037] Figure 8 This is a SEM picture of the size of the biomass carbon nanocavity;

[0038] Fig. 9 This is a SEM picture of the diameter size of the biomass carbon nanocavity in a vertical section. DETAILED DESCRIPTION

[0039] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the protection scope of the present invention is not limited to these embodiments. Any changes or equivalent substitutions that do not deviate from the concept of the present invention are included in the protection scope of the present invention.

[0040] Example 1

[0041] (1) Pine wood was cut into thin slices with a thickness of 0.8 mm and a size of 5 cm*5 cm, and then immersed in a 5 wt% dilute ammonia solution, and refluxed in an oil bath at 120°C for 5 h to remove gum, fatty acids and other substances in the pine wood. The pine wood slices after gum removal were washed 5 times, and free water in the wood slices was removed by vacuum freeze drying; the wood slices were placed in a tubular furnace under the protection of high-purity argon gas and subjected to carbonization treatment at 800°C, with a heating rate of 2°C min -1 , cooling rate 5℃min -1 The heat preservation time at the highest temperature is 5 hours, and a sheet-like porous biomass carbon material with a straight pore structure is obtained. Figure 1 As shown in the plane scanning electron microscope image Figure 8 shown.

[0042] (2) heating the paraffin wax to 100° C. in an oil bath until it is molten, placing the flaky porous biomass carbon material obtained in step (1) in the paraffin wax and immersing it for 3 h, placing the paraffin wax and the flaky porous biomass carbon material in a vacuum drying oven, setting the temperature to 80° C. and the vacuum degree to 15 MPa, and leaving the oven to stand for 3 h to obtain a phase change micro-nano cavity sequence sheet impregnated with hot melt paraffin microchannels;

[0043] (3) 5 wt% graphene oxide slurry was coated by a doctor blade with a blade spacing of 3 mm, and dried at 80° C. to obtain a graphene oxide film with a thickness of 240 μm. The graphene oxide film was cut and graphitized at 3000° C. under argon protection to obtain a graphene foam film, which was then calendered to obtain a density of 2.0 g / cm 3 The graphene thermal conductive film is 60μm thick. The graphene thermal conductive film is die-cut according to the size of the nanocavity sequence sheet, and the edge is annularly attached with a 3mm wide thermal conductive adhesive. The actual graphene thermal conductive film is shown in the figure below. Figure 3 The cross-sectional SEM image is shown in Figure 4 shown.

[0044] (4) The phase change micro-nano cavity sequence sheet obtained in step (2) and the graphene thermal conductive film prepared in step (3) are placed in a mold. The order of placement in the mold is the graphene thermal conductive film paste, the phase change micro-nano cavity sequence sheet impregnated and encapsulated with hot melt paraffin microchannels, and the graphene thermal conductive film paste. The vacuum press is set to a vacuum degree of 15 MPa for 5 minutes, and the gap is filled with liquid paraffin. A 500-ton vacuum press is used for vacuum pressing at 25°C for 10 minutes to seal the mold at the glue pressing position to obtain a graphene composite biomass micro-nano cavity heat sink. The actual measured temperature drop curve test diagram of its 1W stable heat source is as shown in the figure. Figure 7 shown.

[0045] Example 2

[0046] (1) Pine wood was cut vertically into thin slices with a thickness of 0.8 mm and a size of 5 cm*5 cm, and then immersed in a 5 wt% dilute ammonia solution and refluxed in an oil bath at 120°C for 5 h to remove gum, fatty acids and other substances in the pine wood. The wood slices after gum removal were washed 5 times and free water in the wood slices was removed by vacuum freeze drying. The wood slices were placed in a tubular furnace under the protection of high-purity argon and subjected to carbonization treatment at 800°C at a heating rate of 2°C min -1 , cooling rate 5℃min -1 The heat preservation time at the highest temperature is 5h, and a sheet-like porous biomass carbon material with a straight pore structure is obtained. The plane scanning electron microscope image is as follows Fig. 9 shown.

[0047] (2) The process for preparing the paraffin phase change micro-nano cavity sequence sheet is the same as that in Example 1.

[0048] (3) The preparation of graphene thermal conductive film is the same as in Example 1.

[0049] (4) The process of preparing the graphene composite biomass micro-nano cavity heat sink is the same as that in Example 1. The actual temperature drop curve test diagram of the 1W stable heat source is as shown in the figure below: Figure 7 shown.

[0050] Example 3

[0051] (1) Pine wood was cut into thin slices with a thickness of 0.8 mm and a size of 5 cm*5 cm, and then immersed in a 5 wt% dilute ammonia solution, and refluxed in an oil bath at 120°C for 5 h to remove gum, fatty acids and other substances in the pine wood. The wood slices after gum removal were washed 5 times, and free water in the wood slices was removed by vacuum freeze drying; the wood slices were placed in a tubular furnace under the protection of high-purity argon gas and subjected to carbonization treatment at 1200°C, with a heating rate of 2°C min -1 , cooling rate 5℃min -1 The heat preservation time at the highest temperature is 5h, and a flaky porous biomass carbon material with a straight pore structure is obtained.

[0052] (2) The process for preparing the paraffin phase change micro-nano cavity sequence sheet is the same as that in Example 1.

[0053] (3) The preparation of graphene thermal conductive film is the same as in Example 1.

[0054] (4) The process of preparing the graphene composite biomass micro-nano cavity heat sink is the same as that in Example 1. The actual temperature drop curve test diagram of the 1W stable heat source is as shown in the figure below: Figure 7 shown.

[0055] Example 4

[0056] (1) Cut pine wood into 0.8 mm thick 5 cm*5 cm thin slices, soak them in a 5 wt% dilute ammonia solution, reflux them in an oil bath at 120°C for 5 h to remove gum, fatty acids and other substances in the pine wood, wash the wood slices after gum removal for 5 times, and remove free water in the wood slices by vacuum freeze drying; place the wood slices in a tubular furnace under the protection of high-purity argon gas and perform carbonization treatment at 1000°C, with a heating rate of 2°C min -1 , cooling rate 5℃min -1 The heat preservation time at the highest temperature is 5h, and a flaky porous biomass carbon material with a straight pore structure is obtained.

[0057] (2) The process for preparing the paraffin phase change micro-nano cavity sequence sheet is the same as that in Example 1.

[0058] (3) The preparation of graphene thermal conductive film is the same as in Example 1.

[0059] (4) The process for preparing the graphene composite biomass micro-nano cavity heat sink is the same as that in Example 1.

[0060] like Figure 2 As shown in the conductivity diagram of biomass nanocavities treated at different heat levels, the conductivity of Examples 1, 3 and 4 is different at different heat treatment temperatures. The conductivity is lower at 800°C, and the conductivity is not much different at 1000-1200°C. Figure 7 As shown in the test graph of the actual temperature drop curve of its 1W stable heat source, compared with the flat cutting method of pine wood in Example 1 and the vertical cutting method of pine wood in Example 2, the flat cutting method cools down faster, and the temperature of the pine wood carbonized at 1200°C in Example 3 drops lower.

Claims

1. A method for preparing a graphene composite biomass micro-nano cavity heat sink, characterized in that: The following steps are involved: (1) Preparation of sheet-like porous biomass carbon materials with straight pore structures Cut the wood into thin slices and soak them in a dilute ammonia solution, reflux them at 100-150°C, and then carbonize them at 800-1200°C to obtain a flaky porous biomass carbon material with a straight pore structure; (2) Preparation of phase-change micro-nano cavity sequence sheets by hot-melt wax microchannel impregnation The flaky porous biomass carbon material obtained in step (1) is placed in molten paraffin for immersion, and vacuum dried to obtain a phase change micro-nano cavity sequence sheet impregnated and encapsulated with hot melt paraffin microchannels; (3) Preparation of graphene thermal conductive film The graphene oxide slurry is dried to form a film, cut, and graphitized at 2600-3000°C to obtain a graphene foam film, which is then calendered to obtain a graphene thermal conductive film, which is then die-cut and formed, and the edge bonding position is bonded with a thermal conductive adhesive; (4) Graphene thermal conductive film coated micro-nano cavity assembly to prepare heat spreader The phase change micro-nano cavity sequence sheet obtained in step (2) and the graphene thermal conductive film obtained in step (3) are placed in a mold, the gaps are filled with liquid paraffin, and vacuum pressed to obtain a graphene composite biomass micro-nano cavity heat spreader.

2. The method for preparing a graphene composite biomass micro-nano cavity heat sink according to claim 1, characterized in that: The wood used in step (1) is wood of the coniferous tree species, and the slicing method is flat cutting or ring cutting to obtain wood chips with short-diameter dense array tubes, or vertical cutting to obtain wood chips with long-diameter sparse array tubes.

3. The method for preparing a graphene composite biomass micro-nano cavity heat sink according to claim 1, characterized in that: In the step (1), the slices are immersed in a dilute ammonia solution with a concentration of 3-10wt%, refluxed in an oil bath at 100-150°C for 5-8h, washed with water for 3-5 times, and free water in the wood chips is removed by vacuum freeze drying; and then a subsequent carbonization treatment is performed.

4. The method for preparing a graphene composite biomass micro-nano cavity heat sink according to claim 1, characterized in that: In the step (1), the carbonization temperature of the wood chips is set at 800-1200° C., the heat preservation time at the highest temperature is 3-5 hours, and the surface shrinkage ratio of the log and the porous carbon material after carbonization is 3:1-5:

1.

5. The method for preparing a graphene composite biomass micro-nano cavity heat sink according to claim 1, characterized in that: Step (2) The conditions for injecting paraffin wax into the flaky porous biomass carbon material tube are as follows: the paraffin wax is heated to 80-120° C. until it is molten and then fully impregnated with the flaky porous biomass carbon material for 3-5 hours.

6. The method for preparing a graphene composite biomass micro-nano cavity heat sink according to claim 1, characterized in that: In the step (3), 3-5 wt% graphene oxide slurry is dried to form a film to obtain a graphene oxide film with a thickness of 200-380 μm, the graphene oxide film is cut, and graphitized at 2600-3000° C. under argon protection to obtain a graphene foam film, which is calendered to obtain a density of 1.8-2.0 g / cm 3 Graphene thermal conductive film with a thickness of 40-80μm.

7. The method for preparing a graphene composite biomass micro-nano cavity heat sink according to claim 1, characterized in that: In the step (4), the graphene thermal conductive film is die-cut according to the size of the phase change micro-nano cavity sequence sheet, and the edge is annularly bonded with a 1-3 mm wide thermal conductive adhesive. The order of placement in the mold is: graphene thermal conductive film paste, phase change micro-nano cavity sequence sheet impregnated and encapsulated with hot melt paraffin micro-channels, and graphene thermal conductive film paste.

8. The method for preparing a graphene composite biomass micro-nano cavity heat sink as claimed in claim 1, characterized in that: The vacuum degree negative pressure of the vacuum press in the step (4) is set to 5-15 MPa, the vacuuming time is 3-5 min, and the mold is pressed at the gluing position to seal.

9. A method for preparing a graphene composite biomass micro-nano cavity vapor chamber according to any one of claims 1 to 8, characterized in that: The specific steps include: (1) Cut pine wood into slices and soak them in a dilute ammonia solution with a concentration of 3-10wt%, reflux them in an oil bath at 100-150°C for 5-8h to remove gum and fatty acids in the pine wood slices, wash the wood slices after gum removal for 3-5 times, and remove free water in the wood slices by vacuum freeze drying; place the pine wood slices in a tube furnace under the protection of high-purity argon gas and perform carbonization treatment at a temperature of 800-1200°C, with a heating rate of 2°C min -1 , cooling rate 5℃min -1 , the heat preservation time at the highest temperature is 3-5h, and a flaky porous biomass carbon material with a straight pore structure is obtained; (2) heating the paraffin wax to 80-120° C. in an oil bath until the paraffin wax is molten, placing the flaky porous biomass carbon material obtained in step (1) in the paraffin wax and immersing it for 3-5 hours, placing the paraffin wax and the flaky porous biomass carbon material in a vacuum drying oven, setting the temperature to 80-100° C. and the vacuum degree to 5-15 MPa, and drying the flaky porous biomass carbon material in the oven to obtain a phase change micro-nano cavity sequence sheet impregnated with hot melt paraffin wax microchannels; (3) applying a 3-5 wt% graphene oxide slurry by doctor blade coating with a blade spacing of 3-5 mm, drying at 70-90° C. to form a graphene oxide film with a thickness of 200-380 μm, cutting the graphene oxide film, and graphitizing it at 2600-3000° C. under argon protection to obtain a graphene foam film, which is calendered to obtain a density of 1.8-2.0 g / cm 3 Graphene thermal conductive film with a thickness of 40-80μm; The graphene thermal conductive film is used as a packaging shell and is die-cut according to the size of the phase change micro-nano cavity sequence sheet impregnated with hot melt wax micro-channels, and the edge bonding position is attached with thermal conductive glue; (4) placing the phase change micro-nano cavity sequence sheet obtained in step (2) and the graphene thermal conductive film obtained in step (3) into a mold, filling the gap with liquid paraffin, and performing vacuum pressing treatment at 25° C. for 10-30 min using a vacuum press to obtain a graphene composite biomass micro-nano cavity heat spreader.

Citation Information

Patent Citations

  • Graphene-based composite phase change material with graded heat conduction structure and preparation method of graphene-based composite phase change material

    CN113265230A

  • Preparation method of biomass-based temperature control board and prepared temperature control plate

    CN113323170A